Correction: Phylogenetic and histopathological characterization of putative Hepatozoon ophisauri-like lineages in rodents from Italy - Davide Sogliani; Maria Sampieri; Filippo Maria Dini; Mattia Calzolari; Deborah Torri; Valentina Carta; Patrizia Bassi; Alicia Rojas; Giulia Maioli (Acta Parasitologica, 2026)

Phylogenetic and histopathological characterization of putative Hepatozoon ophisauri-like lineages in rodents from Italy - Davide Sogliani; Maria Sampieri; Filippo Maria Dini; Mattia Calzolari; Deborah Torri; Valentina Carta; Patrizia Bassi; Alicia Rojas; Giulia Maioli (Acta Parasitologica, 2026)

TNBS colitis induces architectural changes and alpha-synuclein overexpression in mouse distal colon: A morphological study - Arianna Casini; Giorgio Vivacqua; Ludovica Ceci; Stefano Leone; Rosa Vaccaro; Marco Tagliafierro; Filippo Maria Bassi; Sara Vitale; Emanuele Bocci; Luigi Pannarale; Simone Carotti; Antonio Franchitto; et al. (Cell and Tissue Research, 2025)

A multi-reference parent nested-association mapping population to dissect the genetics of quantitative traits in durum wheat - Samir Alahmad; Yichen Kang; Eric Dinglasan; Dilani Jambuthenne; Hannah Robinson; Yongfu Tao; Jason A. Able; Jack Christopher; Kai P. Voss-Fels; Filippo M. Bassi; Lee T. Hickey (Genetic Resources and Crop Evolution, 2023)

Institutional and farm-level challenges limiting the diffusion of new varieties from public and CGIAR centers: The case of wheat in Morocco - Yigezu A. Yigezu; Zewdie Bishaw; Abdoul Aziz Niane; Jeffrey Alwang; Tamer El-Shater; Mohamed Boughlala; Aden Aw-Hassan; Wuletaw Tadesse; Filippo M. Bassi; Ahmed Amri; Michael Baum (Food Security, 2021)
Low adoption of agricultural technologies slows efforts to increase agricultural productivity and enhance rural livelihoods in developing countries. A large body of literature has sought explanations for the problem, but the focus has been mainly on micro-level farm and community factors affecting adoption. Institutional factors such as policies and market conditions, which are also important, have been largely overlooked and, few, if any, studies combine the two levels of analysis. We use Morocco as a case study to analyze institutional and farm-level factors affecting diffusion and adoption of improved wheat varieties. Results show both sides to be important. Institutional factors such as overly stringent variety testing procedures, imbalance of power among actors in the seed sector and ill-conceived variety licensing contracts limit access to seeds of more recently released varieties. Adoption of older new varieties is found to be affected by farm and farmer characteristics, but imperfect access to new seeds, sometimes associated with the failings identified above, is also a constraint. Findings signal the need for increased private engagement in seed multiplication; revised variety testing procedures; alternative royalty mechanisms; and enhanced linkages between public research and private seed companies.

Effect of temperature on the expression of resistance to Hessian fly (Diptera: Cecidomyiidae) in durum wheat cultivars - Hajar Brahmi; Abderrahim Lazraq; Rachid Boulamtat; Karim El Fakhouri; Filippo Maria Bassi; Mustapha El Bouhssini (Phytoparasitica, 2021)

Development of COS-SNP and HRM markers for high-throughput and reliable haplotype-based detection of Lr14a in durum wheat (Triticum durum Desf.) - Irma Terracciano; Marco Maccaferri; Filippo Bassi; Paola Mantovani; Maria C. Sanguineti; Silvio Salvi; Hana Šimková; Jaroslav Doležel; Andrea Massi; Karim Ammar; James Kolmer; Roberto Tuberosa (Theoretical and Applied Genetics, 2013)

A radiation hybrid map of chromosome 1D reveals synteny conservation at a wheat speciation locus - Monika K. Michalak de Jimenez; Filippo M. Bassi; Farhad Ghavami; Kristin Simons; Rissa Dizon; Raed I. Seetan; Loai M. Alnemer; Anne M. Denton; Münevver Doğramacı; Hana Šimková; Jaroslav Doležel; Kiran Seth; et al. (Functional & Integrative Genomics, 2013)

Wheat Zapper: a flexible online tool for colinearity studies in grass genomes - Loai M. Alnemer; Raed I. Seetan; Filippo M. Bassi; Charith Chitraranjan; Adam Helsene; Paul Loree; Steve Bou Goshn; Yong Q. Gu; Ming-Cheng Luo; M. Javed Iqbal; Gerard R. Lazo; Anne M. Denton; et al. (Functional & Integrative Genomics, 2013)

Comparative transcript profiling of apricot (Prunus armeniaca L.) fruit development and on-tree ripening - George A. Manganaris; Angela Rasori; Daniele Bassi; Filippo Geuna; Angelo Ramina; Pietro Tonutti; Claudio Bonghi (Tree Genetics & Genomes, 2011)

Upper Eocene larger foraminiferal–coralline algal facies from the Klokova Mountain (southern continental Greece) - Filippo Barattolo; Davide Bassi; Roberta Romano (Facies, 2007)

Identification and characterization of transcripts differentially expressed during development of apricot (Prunus armeniaca L.) fruit - Filippo Geuna; Riccardo Banfi; Daniele Bassi (Tree Genetics & Genomes, 2005)